Role of GSK-3 β in Neurodegenerative Disorders - Sagar, Nibha; Saxena, Madhukar (Asian Journal of Biological and Life Sciences, 2013)
Glycogen synthase kinase (GSK-3) is a ubiquitously expressed, highly conserved serine/threonine protein kinase found in all eukaryotes. The GSK-3 was first characterized for its role in glycogen metabolism by phosphorylating and inactivating the enzyme glycogen synthase. There are two mammalian GSK-3 isoforms encoded by distinct genes: GSK-3α and GSK-3β. GSK-3β is involved in the regulation of a wide range of cellular functions including differentiation, growth, proliferation motility, cell cycle progression, embryonic development, apoptosis, and insulin response. Dysregulation of GSK-3β expression leads to many pathological conditions, including diabetes or insulin resistance and neurodegeneration. Here we review on role and association of GSK-3β polymorphisms in different neurodegenerative disorders. Several lines of evidences including association and gene expression studies have suggested GSK-3β as a susceptible gene for neurodegenerative disorders, and its expression alteration caused by the risk SNP in the promoter region may contribute to the etiology of neurodegenerative disorders. This suggests that pertaining to the molecular clock as possible endophenotypes of neurodisorders, and for GSK-3β as a target of a new class of antidepressant drugs.